Tick salivary gland extract-activated transmission of Borrelia afzelii spirochaetes - Pechová, Jitka; Stĕpánová, Gabriela; Kovár, Lubomír; Kopecký, Jan (Folia parasitologica, 2002)
Saliva-activated transmission of Borrelia afzelii Canica, Nato, du Merle, Mazie, Baranton et Postic, 1993 was demonstrated using salivary gland extract (SGE) from Ixodes ricinus (L., 1758) ticks and C3H mice. Injection of Borrelia spirochaetes together with SGE increased the level of bacteraemia and accelerated the appearance of bacteria in the urinary bladder, compared with the injection of spirochaetes alone. More I. ricinus nymphs became infected when feeding on mice inoculated with B. afzelii plus SGE. Analysis of cytokines produced by cells of draining lymph nodes from SGE-treated mice showed a suppression of proinflammatory cytokines IFN-gamma, IL-6 and GM-CSF following a transient upregulation in comparison with the control mice infected without SGE.
Keywords: Arthropod Vectors; klíště; incidence; Borrelia burgdorferi Group; faktor stimulující granulocyto-makrofágové kolonie; močový měchýř; Ixodes; zvířata; ženské pohlaví; Borrelia burgdorferi komplex; Mice, Inbred C3H; Interferon-gamma; interleukin-6; Female; Host-Parasite Interactions; Lyme Disease; Interleukin-6; interakce hostitele a parazita; myši inbrední C3H; Mice; členovci - vektory; lymeská nemoc; myši; Urinary Bladder; interferon gama; Interleukin-10; Incidence; Salivary Glands; Granulocyte-Macrophage Colony-Stimulating Factor; slinné žlázy; Animals; interleukin-10